Most courses are not born digital: An overview of the Quality Matters peer review process for online course design. Issue 4 (2014) - ,
Abstract : Purpose – The purpose of this paper is to discuss benefits of and barriers to online learning and describe utilization of the Quality Matters (QM) peer review process as a method to assure the quality of online courses. It outlines the QM higher education rubric, explains how the collaborative QM peer review process facilitates online course design and certification, reports on the development of a statewide consortium in Ohio, and explores future directions in online courses.Design/methodology/approach – This paper offers a brief historical review of the incorporation of technology into teaching and learning. It describes attitudes toward online learning and the creation of the non‐profit QM program as a vehicle for improving online course design. It summarizes the eight standards of the QM rubric, describes the QM peer review process, and discusses the implementation of the Ohio QM Consortium (OQMC) as a shared services model.Findings – Given existing barriers to online learning, the QM program can improve learning outcomes by offering best practices in online course design, validating the quality of online courses, encouraging faculty buy‐in through a focus on design rather than content, and facilitating degree completion through recognition of quality courses.Practical implications – Institutions that seek to validate online course quality in a cost‐effective manner can explore a shared services model such as that developed by the OQMC.Originality/value – This paper introduces to an international audience a program and process, widely implemented in the USA, which encourages inter‐institutional cooperation and promotes a supportive culture among online educators. Acknowledgements : The author thanks Brenda Boyd, Jillian Jevack, and Orestes Varonis for discussing many of these issues, and the anonymous reviewer whose insightful observations and suggestions enhanced the final version of this paper.